2015
DOI: 10.1002/smll.201502408
|View full text |Cite
|
Sign up to set email alerts
|

Postsynthesis of h‐BN/Graphene Heterostructures Inside a STEM

Abstract: Combinations of 2D materials with different physical properties can form heterostructures with modified electrical, mechanical, magnetic, and optical properties. The direct observation of a lateral heterostructure synthesis is reported by epitaxial in‐plane graphene growth from the step‐edge of hexagonal BN (h‐BN) within a scanning transmission electron microscope chamber. Residual hydrocarbon in the chamber is the carbon source. The growth interface between h‐BN and graphene is atomically identified as largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
1
20
0
1
Order By: Relevance
“…All the peaks of the B, N and C-K edge have been reported in the literature. 23 Therefore, the h-BN-RGO particles have been prepared successfully.…”
Section: Characterization Of H-bn-rgo Hybridsmentioning
confidence: 99%
“…All the peaks of the B, N and C-K edge have been reported in the literature. 23 Therefore, the h-BN-RGO particles have been prepared successfully.…”
Section: Characterization Of H-bn-rgo Hybridsmentioning
confidence: 99%
“…Even though there is a slight mismatch on the crystal lattice of graphene and h-BN (~ 1.7 %), STM and HR-TEM studies indicated that it is possible to achieve a seamless stitching at atomic scale between both (Figure 15b). [33][34][35] The two lattices are then oriented, with the junctions corresponding predominantly to zigzag edges. TEM inspections also showed evidences of hybridization, with bonding occurring between the N atoms of the h-BN and the C atoms of the graphene.…”
mentioning
confidence: 99%
“…[9][10][11] Recent results have shown that EELS at much higher spectral resolution (at or below 20 meV) and at high spatial resolution is possible. 7,[12][13][14] In this letter, we discuss the influence of sample temperature for excitons absorption measurements in TMD using EELS. We show that for MoSe 2 , the two exciton peaks separated by 220 meV are only distinguishable below 220 K and clearly visible at 150 K (for the same experimental conditions).…”
mentioning
confidence: 99%